A novel mutation in SPINK5 gene underlies a case of atypical Netherton syndrome - Wang, Yu; Song, Hanqing; Yu, Lingling; Wu, Nan; Zheng, Xiaodong; Liang, Bo; Wang, Peiguang (Frontiers in Genetics, 2022)
Netherton syndrome (NS, OMIM #256500) is a rare autosomal recessive disease characterized by a triad of congenital ichthyosiform erythroderma (CIE) or ichthyosis linearis circumflexa (ILC), trichorrhexis invaginata (TI), and atopic predisposition. The disease is caused by a mutation in the SPINK5 gene (serine protease inhibitor of kazal type 5) on chromosome 5q32 encoding LEKTI (lymphoepithelial kazal type-related inhibitor). We performed whole exome sequencing on a NS Chinese family and genotype-phenotype correlation analysis in the patients with NS and congenital ichthyosis erythroderma. We identified a novel frameshift mutation c.2474_2475del (p.Glu825Glyfs*2) in the SPINK5 gene. The N-terminal mutations of LEKTI cause a severer phenotype, while the C-terminal mutations of LEKT1 are related to a milder phenotype. Our findings suggest that Netherton syndrome may be underestimated clinically, and further expand the reservoir of SPINK5 mutations in Netherton syndrome.